Military tactics used by the Filipino insurgents - Cave, W. B. (My University, 1908)
Introduction: I have taken for my theme the mode of fighting conducted by the Filipino insurgents, and in order that the reader be not misled by the general belief that all the insurgents are uncivilized, I point out the Tagalos, the Visayas, the Ilacanos and others, all civilized tribes and very formidable enemies.
Citation: Cave, W. B. Military tactics used by the Filipino insurgents. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: War; Philippines; Filipino; Military; Graduating theses; Senior theses; Theses